2021
DOI: 10.3390/geosciences11100404
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the Gorte and Spiaz de Navesele Landslides, NE of Lake Garda, Trentino Dolomites (Italy)

Abstract: We applied a multi-method approach to reconstruct the Gorte rock avalanche (85–95 Mm3) located at the northeastern end of Lake Garda. The combination of field mapping, characterization of bedrock discontinuities, Dan3D-Flex runout modeling and dating of boulders with cosmogenic 36Cl supports the conclusion that the deposits stem from a single rock avalanche at 6.1 ± 0.8 ka. The Gorte event may have triggered the Spiaz de Navesele–Salto della Capra landslide (3.2 Mm3), whose deposits cover the southern end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…A better understanding of rock avalanche occurrence and motion requires detailed analysis of a large number of case histories (e.g., Evans et al 1994;Nagelisen et al 2015;Grämiger et al 2016;Ivy-Ochs et al 2017;Singeisen et al 2020). As rock avalanches are infrequent events, studies of pre-historic rock avalanches provide crucial information regarding rock avalanche geomorphology and sedimentology (e.g., Cruden and Hungr 1986;Giorgio et al 1991;Dufresne et al 2016), runout mechanisms (e.g., Evans et al 1994;Nagelisen et al 2015;Castleton et al 2016;Grämiger et al 2016;Aaron et al 2020), and temporal occurrence (e.g., Ivy-Ochs et al 2017;Ruggia et al 2021), especially for the rare extreme volume event. In particular, detailed mapping of prehistoric rock avalanches has revealed that the source zone stratigraphy often remains intact in the highly comminuted deposit (e.g., Strom 2006, Dufresne et al 2016Singeisen et al 2020;Pfiffner 2022).…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of rock avalanche occurrence and motion requires detailed analysis of a large number of case histories (e.g., Evans et al 1994;Nagelisen et al 2015;Grämiger et al 2016;Ivy-Ochs et al 2017;Singeisen et al 2020). As rock avalanches are infrequent events, studies of pre-historic rock avalanches provide crucial information regarding rock avalanche geomorphology and sedimentology (e.g., Cruden and Hungr 1986;Giorgio et al 1991;Dufresne et al 2016), runout mechanisms (e.g., Evans et al 1994;Nagelisen et al 2015;Castleton et al 2016;Grämiger et al 2016;Aaron et al 2020), and temporal occurrence (e.g., Ivy-Ochs et al 2017;Ruggia et al 2021), especially for the rare extreme volume event. In particular, detailed mapping of prehistoric rock avalanches has revealed that the source zone stratigraphy often remains intact in the highly comminuted deposit (e.g., Strom 2006, Dufresne et al 2016Singeisen et al 2020;Pfiffner 2022).…”
Section: Introductionmentioning
confidence: 99%